Peran Kepala Madrasah dalam Meningkatkan Etos Kerja Guru - Ahmad Syukri; Nuzuar Nuzuar; Idi Warsah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to determine the role of the principal in improving teacher performance. Research uses a field research approach (field research). The results of the study, the headmaster always supervises or supervises by going around the classroom to see the teacher. In addition to supervising the teaching of the madrasah head teacher also plays a role in the process of monitoring or evaluating the work of all staff in the madrasah including the teacher, the madrasa head tries to influence teachers and employees to encourage enthusiasm for work and commitment to the task objectives. The conclusion of this research is the madrasa head plays an active role in efforts to improve the work ethic of teachers, namely by establishing harmonious relationships with fellow teachers (teachers), providing welfare to teachers who accommodate, control and evaluate teachers in carrying out their tasks so that they can change mindsets in building the character of the teacher, so that the teachers helped build the madrasas to be the foremost in accordance with their vision and mission. Keywords: The Principal's Role, Teacher's Work Ethic